Brief grouptherapy of multiple couples in day hospital - Motta, Lenise Freitas (2002)
The Group Psychotherapy with Couples (GPC) as a specific modality of treatment in a public Day Hospital of the University was implanted in 1997, with the objective of placing the couple as treatment intervention pole, and support it in a crisis situation, with one of the partners in partial admission at the institution. The present study aims to describe this modality of treatment, through the observation of eleven consecutive psychotherapy sessions, recorded in video and later transcribed. The data were analyzed according to thematic categorical content analysis. It was observed that it is a support group, with intense participation of the therapists, who actively stimulated the couples and act providing information, and with the participants in one more passive role, bringing themes related to the familiar quotidian and difficulties in leading with the partner pathology. It is concluded that the group allows specific support to elaborate the relationship among partners in crisis.